PENGEMBANGAN METODE SIMULASI SISTEM PENGKONDISIAN UDARA ENERGI SURYA - Hermanto, Agus; Suwono, Aryadi; Abdurrachim, Abdurrachim; Pasek, Ari D (Mesin, 2005)
In this research, a simulation method has been developed for designing a solar air conditioner and predicting its perfomances. This simulation based on solar irradiation data, solar collector performance data, LiBr-H2O absorption chiller single effect performance data, Phase Change Material (PCM) data as its inputs. Napthalene is used for HTTS and acetic acid is used for TTS. Energy balance, mass balance, and characteristic equations of each component are used in the solar air conditioning simulation. Validation of the developed simulation model was done with experiment data for solar air conditioning system with HTTS and LTTS without auxiliary heater. Generally, the tendency of the simulation and experiment results are similar. The application of HTTS and LTTS make the system can be operated more in 100 minutes.